FENOMENA KEJUT BUDAYA (CULTURE SHOCK) PADA MAHASISWA RANTAUAN DI FISIP UNIVERSITAS UDAYANA - Mulya Astari, Gusti Ayu Agung Chandra; Zuryani, Nazrina; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI: SOROT, 2020)
ABS TRACT   Most o f s tudent at F I S IP Unud are s tudents m i grants. T h i s r esearch took two problem formulations; how i s the c u l ture s hock phenomenon experienced by t he s t udents migrants a t t he F aculty o f S ocial and P olitical S ci ences, U dayana U niversity a nd how the s tudents m i grants overcome c ultural s h ock i n their new environment. T h e theory i n t his s tudy i s the thought of a n anthropologist K alvero O b erg i n t he 1960s. T h e r esult from the r esearch that the s tudents migrants experienced c u l ture s hock by s everal f actor, s uch as: s osio-cultural factors, environmental factors, c u l i nary and tourism f actors a nd h omesickness. T here are s everal ways to overcome t he c ultural s hock that are done by t he s tudents migrants which i s different o nto each other’s according to t he personality of e ach i ndividual e.i: a dapting l ocal c ommunication through l a nguage adjustment the way l ocals c ommunicate, l earn a nd try to fit i n the new c ulture, follow w hich happened to b e popular i n their n ew e nvironment.   Keywords :   Culture  S h o ck ,  S tud ent  M igrants ,  C r i sis  Cultural .